TROP2 LEVEL IMPORTANCE AS PROGNOSTIC VALUE IN BREAST CANCER PATIENTS (Journal of Pharmaceutical Negative Results, 2023)
Background: Breast cancer (BC) is disease effected the breast tissue , it's onset at female more than male . The diagnosis of BC depend on oncology guideline included clinical , radiological and laboratory examination . Trophoblast cell surface antigen 2 (TROP2) is glycoprotein molecular act as trans-membrane receptor encoded and synthesized via tumor associated Ca signal transducer 2 (Tacstd2) gene that located on chromosome 1p32 . Objective of the Study: At this study explain high TROP2 marker expression in malignant BC patients via used Immunohistochemical method , and use it as prognostic value for BC disease . Materials and Methods: This study is done at Al-Yarmook Teaching Hospital from ........ 2020 to .....2022 , included 60 individuals classified into malignant and non-malignant of BC .All individuals applied under examinations then detected presence of TROP2 marker via Immunohistochemical method . Results: Present study appeared high different value for TROP2 marker expression between malignant and non-malignant BC groups . TROP2 expression was high percent in malignant BC group compared with non-malignant group. Conclusion: The present study confirmed role of TROP2 marker expression at BC progression and used it as prognostic value to BC disease .